2021
DOI: 10.1136/bjophthalmol-2020-318491
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month outcomes of ranibizumab versus aflibercept for macular oedema in branch retinal vein occlusion: data from the FRB! registry

Abstract: Background/AimsTo compare the efficacy of ranibizumab (0.5 mg) with aflibercept (2 mg) in the treatment of cystoid macular oedema due to branch retinal vein occlusion (BRVO) over 12 months.MethodsA multicentre, international, database observational study recruited 322 eyes initiating therapy in real-world practice over 5 years. The main outcome measure was mean change in EDTRS letter scores of visual acuity (VA). Secondary outcomes included anatomic outcomes, percentage of eyes with VA >6/12 (70 letters), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…registry which were treated with either ranibizumab or aflibercept. 3 The mean change in VA from a similar mean baseline in this RWS (+10.9 letters) was comparable to that observed in the current study with a similar number of injections having been administered (median also seven). Similarly, the mean CST improvement for BRVO eyes in our study of À149 μm was within the range reported in the cohorts treated with aflibercept (À170 μm) or ranibizumab (À147 μm).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…registry which were treated with either ranibizumab or aflibercept. 3 The mean change in VA from a similar mean baseline in this RWS (+10.9 letters) was comparable to that observed in the current study with a similar number of injections having been administered (median also seven). Similarly, the mean CST improvement for BRVO eyes in our study of À149 μm was within the range reported in the cohorts treated with aflibercept (À170 μm) or ranibizumab (À147 μm).…”
Section: Discussionsupporting
confidence: 85%
“…This hypothesis is supported by the recent analysis of eyes with BRVO in the FRB! registry which were treated with either ranibizumab or aflibercept 3 . The mean change in VA from a similar mean baseline in this RWS (+10.9 letters) was comparable to that observed in the current study with a similar number of injections having been administered (median also seven).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, this study compared Faricimab against a low dose of ranibizumab (0.3 mg). In addition, it would be interesting to compare Faricimab with aflibercept, which has been shown to be more effective than ranibizumab in DME treatment [95]. The 1-year results of the ongoing 2-year YOSEMITE and RHINE multicenter, randomized trials showed promising results for faricimab in DME [96,97].…”
Section: Other Anti-angiogenic Agentsmentioning
confidence: 99%